دراسة تحليلية لنماذج حوكمة الشركات - الآليات ونظام التشغيل- - كموش, عبد المجيد (جامعة الوادي - University of Eloued, 2018)
يهدف هذا البحث إلى الوقوف على مكونات ومحددات نظام حوكمة الشركات، وكذا تحديد آليات تفعيل هذا النظام، بالإضافة إلى التعرف على أهم النماذج الدولية الرائدة في المجال، ومن ثم الإشارة إلى التجربة الجزائرية في مجال حوكمة الشركات. أظهر البحث أن التمايز في طبيعة وخصوصية الأنظمة السائدة والنماذج الرائدة لحوكمة الشركات مصدره الأساسي هو اختلاف منطق عمل كل آلية من آليات حوكمة الشركات، وتمايز حجم وطريقة تأثيرها بناءً على طبيعة وظروف البيئة الاقتصادية المطبق فيها. The research aims to achieve the key objectives of which stands on components and determinants of corporate governance system, determine mechanisms for activating the corporate governance systems, identify the most important international models in corporate governance, and highlighting the Algerian experience in corporate governance practices. The study revealed that the primary source of variation in nature and privacy of systems and models of corporate governance is the variation in the work of each mechanism of corporate governance, and the differentiation of the size and the method of its impact depending on the nature and circumstances economic environment where applicable.
An analytical study of corporate governance models: Mechanisms and operating system
مقال
Keywords: حوكمة الشركات، نظام حوكمة الشركات، نماذج حوكمة الشركات، حوكمة الشركات في الجزائر; Corporate governance; corporate governance system; corporate governance models; corporate governance in Algeria